ChemInform Abstract: Enantioselective Synthesis of Tertiary α‐Hydroxy Phosphonates Catalyzed by Carbohydrate/Cinchona Alkaloid Thiourea Organocatalysts. Issue 5 (13th February 2013) - Kong, Shasha; Fan, Weidong; Wu, Guiping; Miao, Zhiwei
Abstract The cyanation of β‐ketophosphonates with TmsCN in the presence of organocatalyst CCT and p‐nitrophenol as additive affords α‐trimethylsilyloxy‐α‐cyanophosphonates, which under acidic hydrolysis are quantitatively converted into the desired alcohols.